2021
DOI: 10.5588/ijtld.21.0034
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary TB and chronic pulmonary aspergillosis: clinical differences and similarities

Abstract: BACKGROUND: Pulmonary TB (PTB) and chronic pulmonary aspergillosis (CPA) are both progressive and debilitating parenchymal lung diseases with overlapping risk factors, symptomatology and radiological findings that often result in misdiagnosis of either disease.METHODS: We undertook a narrative review approach to describe the clinical and radiological manifestations of CPA and PTB and highlight the salient features that differentiate these two closely related maladies.RESULTS: CPA is a frequent complication of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 0 publications
2
28
0
Order By: Relevance
“…This is consistent with previously published cases from the rest of the world [6,9,55]. PTB and CPA share several important features-both being progressive parenchymal diseases with overlapping risk factors, symptoms and radiological findings that often lead to misdiagnosis of both disease [5,8,56]. In fact, in most low-and middle-income countries where the index of clinical suspicion and diagnostic capabilities are still low, CPA is managed as smear negative-TB.…”
Section: Discussionsupporting
confidence: 91%
“…This is consistent with previously published cases from the rest of the world [6,9,55]. PTB and CPA share several important features-both being progressive parenchymal diseases with overlapping risk factors, symptoms and radiological findings that often lead to misdiagnosis of both disease [5,8,56]. In fact, in most low-and middle-income countries where the index of clinical suspicion and diagnostic capabilities are still low, CPA is managed as smear negative-TB.…”
Section: Discussionsupporting
confidence: 91%
“… 4 There are many similarities between PTB and CPA in terms of risk factors, clinical presentation, and radiological features, making the two diseases clinically indistinguishable. 5 This may result in misdiagnosis of CPA as PTB, or vice versa. As PTB is more common and largely recognised globally, the index of suspicion for PTB is likely higher compared to CPA, particularly in settings with a high PTB burden.…”
Section: Introductionmentioning
confidence: 99%
“…Being mostly diagnosed as a post-PTB complication, CPA may be misdiagnosed as relapsed PTB infection and managed as such. 5 CPA may also be occasionally misdiagnosed as primary TB infection. 5 Some studies have reported CPA misdiagnosed as acid-fast bacilli (AFB) smear-negative or GeneXpert Mycobacterium tuberculosis (MTB)-negative PTB and resulting in worsening symptoms and anti-TB treatment failure.…”
Section: Introductionmentioning
confidence: 99%
“…Another example is the fungus A. fumigatus , described as responsible for the extracellular synthesis of extremely small (0.68 nm) cube-shaped AgNPs [ 15 ]. Nonetheless, this genus is also responsible for a parenchymal lung disease called aspergillosis [ 56 ].…”
Section: Discussionmentioning
confidence: 99%